Gibraltar and the European Economic Community (EEC): A political history of the impact of European integration on the territory, 1957 to 1987 - Norton, Thomas H. J. (2023)
This thesis examines the political impact of European integration on Gibraltar, which joined the European Economic Community (EEC), alongside the UK, in 1973. Between 1957 and 1987, this ‘European factor’ exerted an enormous influence on Gibraltar’s internal politics; the nature of the frontier with Spain; and Anglo-Spanish relations. Using all the available records at The National Archives and elsewhere, this thesis fills a gap in the historiography by detailing precisely how Gibraltar’s EEC membership came about, and how Spain’s path to membership impacted Gibraltar. Examining this pivotal period through the European lens offers a fresh perspective on familiar events. The deterioration in relations with Spain from 1964 onwards is linked to Britain and Spain’s exclusion from the EEC. Gibraltar’s 16 years of isolation may have ended sooner had Britain pursued its original aim of including Gibraltar within the EEC customs territory. Bilateral talks on Gibraltar’s future in Strasbourg, Lisbon and Brussels, were driven by the need to end the frontier restrictions before Spain’s accession. While the end of the AACR’s long dominance of local politics, and the concomitant rise of a new Gibraltarian nationalism, was a response, in part, to fear of European-led osmosis with Spain.